2014
DOI: 10.1063/1.4869436
|View full text |Cite
|
Sign up to set email alerts
|

Zoned near-zero refractive index fishnet lens antenna: Steering millimeter waves

Abstract: 24/06/14 meb. Publisher version Ok to add

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
(35 reference statements)
3
27
0
Order By: Relevance
“…Such metamaterial has been used for advanced lens design and its good performance has been confirmed in previous works [10][11][12][13][14][15][16][17]. Due to the leaky-wave mechanism present in the fishnet metamaterial, it has the potential to lower insertion loss [8,16].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Such metamaterial has been used for advanced lens design and its good performance has been confirmed in previous works [10][11][12][13][14][15][16][17]. Due to the leaky-wave mechanism present in the fishnet metamaterial, it has the potential to lower insertion loss [8,16].…”
Section: Introductionmentioning
confidence: 72%
“…The equivalent refractive index for a finite number of plates varies with the number of periods due to the inhomogeneity of the fishnet metamaterial [18][19][20]. Considering our previous experience we use four plates (plus one dielectric plate as a protection cover), since it is a good trade-off between total thickness and electromagnetic performance in terms of insertion loss [10][11][12][13][14][15][16]. Therefore, the total thickness of the structure is w = 4t m + 5t d = 1.97 mm (~0.62 k 0 ).…”
Section: à4mentioning
confidence: 99%
“…27 This concept has been commonly applied in the design of zoned dielectric lenses and it has been proposed and experimentally demonstrated at millimeter-waves in all-metallic fishnet metalenses. [28][29][30][31] The zoning technique relies on the fact that redundant phase advance of 2π of the waves traveling inside of the lens does not contribute to the focusing. Thus, the lens section causing it can be removed.…”
Section: Zoned Metalensmentioning
confidence: 99%
“…Furthermore, the higher side lobe level is obtained for an output angle of 18º in the experiment with a value of -4.85 dB, which is closer to the main lobe compared with the other angles. The experimental gain (defined as the ratio of the radiated power density in the direction of maximum emission and the power density radiated by an ideal lossless isotropic radiation that emits all the power fed by the source 26 ) at the working frequency (144 GHz) has a maximum of 11 dB at 0º, which is obtained comparing the ENZ-lens with a horn antenna using the comparison method 30 . Moreover, it is shown that the maximum normalized radiation power at 18º is below -3dB, which is used as a standard of the maximum scan loss allowed for a suitable beam steering.…”
mentioning
confidence: 99%
“…Nevertheless, it is in the field of lenses where they have been more intensively investigated. [15][16][17][18] Unlike other metamaterial lenses, 15,[19][20][21][22][23][24][25][26][27] narrow hollow waveguides based ENZ lenses offer reduced reflection losses due to the squeezing/tunneling/supercoupling effect-induced impedance matching with free space. 16,17 In addition, ENZ-lenses realized by all-metallic narrow hollow rectangular waveguides have several advantages in comparison with lenses made partially or wholly from dielectrics, such as resistant to hazardous conditions and higher operation power.…”
mentioning
confidence: 99%